Effects of Harvesting Age and Barley Varieties on Morphological Characteristics, Biomass Yield, Chemical Composition, and Economic Benefits under Hydroponic Conditions in Fogera District, Ethiopia - Yeshambel Alemnew; Yeshambel Mekuriaw (Advances in Agriculture)
The objectives of this study were to evaluate the effects of harvesting age at 6, 8, 10, and 12 days and four barley varieties HB-1307, Debark-1, Tila, and local varieties on morphological characteristics, biomass yield, chemical composition, and economic benefits under hydroponics in the Fogera district at Fogera National Rice Research and Training Center of Amhara Region, Ethiopia. The interaction effects of harvesting age and barley variety significantly influenced growth parameters of plant height, shoot length, leaf length, and overall chemical composition (P<0.05). All morphological characteristics were significantly different (P<0.01) among harvesting ages, and the stem weight, leaf to stem ratio (LSR), and number of leaves per plant were not significantly influenced (P>0.05) by the different barley varieties. The highest plant height (21.26 cm) and crude protein (CP) content (21.39%) were obtained from Debark-1 at 12 days of harvesting. The highest fresh fodder biomass yield, 203.50 t/ha, and dry matter (DM) yield, 36.21 t/ha, were obtained at 12 days of harvesting. In the case of harvesting age, all morphological parameters increased with the progress harvesting age, except for the LSR and DM content. The highest net return of 2,923,002.25 ETB/ha was obtained from Debark-1 at the 12 days harvesting age, and the lowest 941,201.13 ETB/ha was obtained for the Tila variety at the six days of harvesting age. From the study, it can be concluded that based on fresh fodder biomass yield, DM yield, CP, and economic benefits, Debark-1 was the recommended barley variety on the 12-day harvesting age, followed by HB-1307, local, and Tila barley varieties.